Penentuan Debit Lingkungan Di DAS Dodokan Berdasarkan Metode Tennant Dan Flow Duration Curve (FDC): Determination Of Environmental Flow In Dodokan Watershed Based On Tennant And Flow Duration Curve (FDC) Method - Muhammad Khalis Ilmi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Dodokan Watershed (DAS) is a watershed that is included in one of the national priority watersheds, so it is necessary to monitor and evaluate the watershed management on a regular basis. One very important aspect in monitoring and evaluating watershed management is the determination of the amount of environmental discharge. Environmental discharge in Indonesia is known as river maintenance flow which is intended in the context of river management to maintain river ecosystems. The amount of river maintenance flow in Indonesia is regulated in PP No. 38 of 2011 concerning rivers, namely Q95% mainstay discharge. The purpose of this study was to determine the amount of environmental discharge in the Dodokan watershed as one of the river management efforts in the future. The method used is the hydrological method, namely the Tennant method and flow duration curve (FDC). The Tennant method recommends that the minimum flow is set relative to the annual average flow and in the FDC method the daily discharge data is processed into a certain percentage as the probability value of the event using Weibull theory. The results showed that the environmental discharge interval using the Tennant and FDC methods was 0.01–0.2 m3/s, from this interval it can be seen that the flow characteristics in the Dodokan watershed have a very small minimum quantity. This situation illustrates that the carrying capacity of the Dodokan watershed is in a declining condition so it is necessary to carry out proper watershed management in accordance with existing conditions